EMERGENCY CRICOTHYROIDOTOMY PROCEDURE: LECTURE ON SURGICAL ANATOMY AND BRIEFING OF THE PROCEDURE FOLLOWED BY SKILL ASSESSMENT IN FIRST SEMESTER MEDICAL STUDENTS - Anasuya Ghosh; Subhramoy Chaudhury (Asociación Argentina de Anatomía Clínica, 2021)
Introduction: Emergency Cricothyroidotomy (ECT) is a life-saving procedure where the cricothyroid membrane is incised to access the larynx to establish breathing in 'can't intubate, can't ventilate' situations. This procedure can be taught along with midline neck anatomy to the first semester medical students and their understanding and application of knowledge could be assessed on cadavers. Materials and methods: Total three sessions was organized to expose and assess the first semester medical students about the Emergency Cricothyroidotomy (ECT) procedure. In each session, a two hour long integrated lecture was delivered regarding the surgical anatomy and the procedure. After that, randomly selected students were assigned a cadaver to locate and puncture the cricothyroid membrane with a sharp pointed wide probe. The time was recorded and pre and post session questionnaire was distributed and response was analysed. Result: The total study participants were 154. Analysis revealed knowledge and confidence of performing the procedure was statistically significantly increased (p <0.005) among the participants after the session. 90% participants successfully pierced the cricothyroid membrane as a team and the average time was 2 minutes 35 seconds. The most students gave a 'good' or 'very good' rating of this session. Conclusion: The medical students should be exposed to emergency life-saving procedures in relation to their anatomy course in earlier days of medical school. This could make them aware and oriented about the procedures which could be beneficial during their clinical training.